Conserved Role of the Large Conductance Calcium-Activated Potassium Channel, KCa1.1, in Sinus Node Function and Arrhythmia Risk. (25th February 2021) - Pineda, Santiago; Nikolova-Krstevski, Vesna; Leimena, Christiana; Atkinson, Andrew J.; Altekoester, Ann-Kristin; Cox, Charles D.; Jacoby, Arie; Huttner, Inken G.; Ju, Yue-Kun; Soka, Magdalena; Ohanian, Monique; Trivedi, Gunjan; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: KCNMA1 encodes the α-subunit of the large-conductance Ca 2+ -activated K + channel, KCa 1.1, and lies within a linkage interval for atrial fibrillation (AF). Insights into the cardiac functions of KCa 1.1 are limited, and KCNMA1 has not been investigated as an AF candidate gene. Methods: The KCNMA1 gene was sequenced in 118 patients with familial AF. The role of KCa 1.1 in normal cardiac structure and function was evaluated in humans, mice, zebrafish, and fly. A novel KCNMA1 variant was functionally characterized. Results: A complex KCNMA1 variant was identified in 1 kindred with AF. To evaluate potential disease mechanisms, we first evaluated the distribution of KCa 1.1 in normal hearts using immunostaining and immunogold electron microscopy. KCa 1.1 was seen throughout the atria and ventricles in humans and mice, with strong expression in the sinus node. In an ex vivo murine sinoatrial node preparation, addition of the KCa 1.1 antagonist, paxilline, blunted the increase in beating rate induced by adrenergic receptor stimulation. Knockdown of the KCa 1.1 ortholog, kcnma1b, in zebrafish embryos resulted in sinus bradycardia with dilatation and reduced contraction of the atrium and ventricle. Genetic inactivation of the Drosophila KCa 1.1 ortholog, slo, systemically or in adult stages, also slowed the heartbeat and produced fibrillatory cardiac contractions. Electrophysiological characterization of slo -deficient flies revealed bursts of action potentials, reflecting increased events of fibrillatory arrhythmias. Flies with cardiac-specific overexpression of the human KCNMA1 mutant also showed increased heart period and bursts of action potentials, similar to the KCa 1.1 loss-of-function models. Conclusions: Our data point to a highly conserved role of KCa 1.1 in sinus node function in humans, mice, zebrafish, and fly and suggest that KCa 1.1 loss of function may predispose to AF.